Exogenous Cytokinins Regulate Nitrogen Metabolism in Soybean Under Low Phosphorus Stress - Yubo Yao; Yongguo Xue; Jun Yan; Xiaofei Tang; Dan Cao; Wenjin He; Xiaoyan Luan; Qi Liu; Zifei Zhu; Xinlei Liu (Agronomy)
Low phosphorus (P) stress impacts nitrogen (N) metabolism in soybeans. This study investigated the effects of exogenous cytokinin (Trans-Zeatin) on soybean N metabolism under low P stress by treating seeds with Trans-Zeatin and analyzing N accumulation, 15N abundance, nodule N fixation accumulation, nodule N fixation rate, nodule nitrogenase activity, soluble protein content, and free amino acid profiles. The results showed that exogenous cytokinin enhanced N accumulation in aboveground tissues, roots, and nodules, as well as nodule N fixation accumulation and fixation rate (from day 35 onward) under low P stress. Additionally, it promoted both acetylene reduction activity (ARA) and specific nitrogenase activity (SNA) in soybean nodules. By increasing the absorption of fertilizer-derived N, exogenous cytokinin alleviated the inhibitory effects of low P stress on the early growth and development of soybeans. Notably, under low P conditions, exogenous cytokinin significantly elevated the soluble protein content in nodules. However, the underlying mechanisms governing changes in free amino acid profiles require further investigation. This study provides a theoretical foundation for developing strategies to regulate soybean N metabolism under low P stress.